THE INFLUENCE OF INDEPENDENT ATTITUDE ON THE DECISION BECOMING AN ENTREPRENEUR WITH ENTREPRENEURIAL KNOWLEDGE AS A MODERATING VARIABLE - Prajogo, Uke; Arda Purnama Putra (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
The purpose of this study was to examine the effect of an independent attitude on the decision to become an entrepreneur with entrepreneurial knowledge as a moderating variable. The type of research used was quantitative with questionnaire data distribution. The population and sample in this study amounted to 50 young entrepreneurs in Malang City. The data analysis method used SPSS assistance. The results showed that an independent attitude had a significant positive effect on the decision to become an entrepreneur. Entrepreneurial knowledge moderates the effect of an independent attitude on the decision to become an entrepreneur